ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - BR Sitinjak, Tio Resta; L. Tobing, Vargo Christian (LPPM Universitas Putera Batam, 2020)
The financial statements provided by each company are an important source of information in the investment business, the regulations set by BAPEPAM number : KEP-431/BL/2012 which states that companies must submit financial reports no later than four months after the end of the year.This study aims to determine the variable profitability, liquidity, company size on the timeliness of financial statement submission. The data used are secondary data in the form of annual reports for the period of 2015-2019 listed on the Indonesia Stock Exchange and the sampling technique using purposive sampling method. Based on the sample criteria, there were 14 samples. The analytical method used in this study is logistic regression and The results of the study were tested using the SPSS version 25 application. The results of this study indicate that partially profitability, liquidity and company size or simultaneously did not significantly influence the timeliness of financial statement submission.